Khasi Phonetic Reader - Nagaraja, K.S. (Central Institute of Indian Languages Mysore, 1990)
Khasi Phonetic Reader helps the learners of the language to understand the scientific pronunciation methods and patterns of the language.
Keywords: Khasi; Phonetic Reader; Bharatavani; Knowledge Through Indian Languages; Phonetic Reader; English